Down‐regulated expression of miR‐134 contributes to paclitaxel resistance in human ovarian cancer cells. Issue 20 (9th September 2015) - Shuang, Ting; Wang, Min; Shi, Cong; Zhou, Yingying; Wang, Dandan
Abstract : MiR‐134 has been reported to have a role in the development and progression of various cancers. In this study, we found that miR‐134 expression was significantly decreased in chemo‐resistant serous epithelial ovarian cancer (EOC) patients. Over‐expression of miR‐134 enhanced the sensitivity of SKOV3‐TR30 cells to paclitaxel, and increased paclitaxel‐induced apoptosis. Further, Pak2 was identified as a direct target of miR‐134, and Pak2‐specific siRNA increased cell inhibition rate and promoted paclitaxal‐induced apoptosis. By regulating Pak2 expression, miR‐134 could mediate Bad phosphorylation at Ser112 and Ser136, which affected cell survival and apoptosis. In conclusion, our findings indicate that repression of miR‐134 and consequent up‐regulation of Pak2 might contribute to paclitaxel resistance. Abstract : miR‐134 was decreased in chemo‐resistant serous epithelial ovarian cancer. miR‐134 by regulating Pak2 affect SKOV3‐TR30 paclitaxel sensitivity and apoptosis. miR‐134 by regulating Pak2 might phosphorylate Bad into Bad‐112, and Bad‐136.